Investigation of the dragging stress of aluminium under cyclic loading - Shota HASUNUMA; Tomoyuki HAYASE (Mechanical Engineering Journal)
The effect of the variation of the dislocation velocity on the dragging stress of aluminium under cycling loading has been investigated. Hydrogen diffusion around a dislocation was simulated by the finite difference method, and the dragging stress was calculated from the hydrogen distribution. The velocity of the dislocation changed in a sinusoidal manner. The dragging stress depended on the frequency of the sinusoidal velocity variation. In the low-velocity region, the maximum dragging stress decreased with increasing frequency. However, in the mid-velocity region, the maximum dragging stress increased with increasing frequency. The dragging stress did not depend on the frequency in the high-velocity region. A dragging stress model for aluminium with hydrogen under a variable dislocation velocity is proposed. When the frequency is below 0.2 kHz (i.e., in general fatigue tests), the dragging stress–velocity relationship under a constant velocity of the dislocation in the case of aluminium with hydrogen can be used. In the high-velocity region, the dragging stress can be determined using the relationship between the dragging stress and velocity under a constant velocity of the dislocation. The dragging stress under the low-velocity condition can be modelled using an ordinary viscosity model. In the case of actual hydrogen concentration, the dragging stress is thought to be much smaller than 1 MPa.